Cooperation and innovation in social economy companies Desarrollo local: reflexiones desde el desarrollo humano sostenible - Celso Vargas Elizondo; Juan Rafael Hernández Navarro (Tecnología en Marcha)
This essay is a social and epistemological reflection on local economic development issued from the perspective of sustainable human development. It deals with some typical problems of development; and a differentiation is established expecting to suggest a road to the status of social citizenship and the threats that this aspiration conveys as well as an analysis of common insertion situations. As an exploratory essay, its main objective is to promote a theoretical reflexion on local economic development.At the same time,it gives an important relative weight to those strategies oriented to include that social sectors more vulnerable in the current process of globalisation. El presente documento contiene una reflexión epistemológica y social del tema del desarrollo económico local, desde la perspectiva del desarrollo humano sostenible. En él se abordan problemas típi- cos del desarrollo; se establece su diferenciación con la expectativa de insinuar al menos las vías de acce- so a la condición de ciudadanía social, las amenazas que esta aspiración experimenta y un recorrido por diversas situaciones de inserción que se suelen presentar. Es, pues, un ensayo exploratorio con el objetivo de promover la reflexión teórica sobre este importante tema. Otorga un gran peso relativo a las estrategias orientadas a incluir económica, social y políticamente a los sectores más vulnerables, en actual proceso de globalización.